PENYULUHAN KESEHATAN TENTANG GIZI SEIMBANG PADA ANAK SEKOLAH DASAR - Sinaga, Megasilvia; Purba, Dewi; Simanjuntak, Mery Lestari (Jurnal Masyarakat Indonesia (Jumas), 2025)
Nutrition is the most important thing in the process of growth and development of children. Nutritional problems such as undernutrition, such as iron and other important vitamin deficiencies, can negatively impact a child's concentration on learning, immunity, and cognitive ability. The purpose of this research is to provide health education in the form of counseling to elementary school children about balanced nutrition.The activity was carried out at UPT SD Negeri 019 Lumban Purba on Thursday, November 14, 2024. The material provided was about Balanced Nutrition for Elementary School Children. The method of providing information is carried out by way of lectures with the help of leaflets instruments.The results of the study showed that the provision of health education about nutrition with the lecture method was proven to be effective in increasing the level of knowledge and involvement of teachers in inviting children to live a healthy lifestyle so that children's nutrition remained balanced, especially during their growth and development. Participants already understand that careless snacks are not good for their nutrition and teachers will start inviting students to bring snacks from home to school more often as snack substitutes. The conclusion in this study is that counseling on balanced nutrition is quite effective in increasing students' knowledge and teachers' involvement in maintaining students' diets.